Ending the Oppression Olympics: Promoting the Concomitant Political Participation of Marginalised Groups in Kenya (Strathmore Law Journal, 2021)
The 2010 Constitution of Kenya is laudable for its commitment to redressing the exclusion from political and public life experienced by marginalised groups. Articles 21 and 27 require that the state and public officials take legal and administrative measures to ensure marginalised groups’ participation in governance and other spheres of life. Moreover, Article 100 mandates the passing of a single legislation to provide for the representation in Parliament of women, youths, persons with disabilities, ethnic minorities and marginalised communities. These provisions evince an intention that their inclusion be redressed simultaneously.However, the equality debate appears to have become synonymous with gender equality or the implementation of the ‘two-thirds gender rule’ as it is popularly known. This rule requires that not more than two-thirds of any elective or appointive position be occupied by one gender. Women’s underrepresentation has dominated litigation on inclusion, academic writing and proposals for electoral reforms.This unitary approach to inclusion, which privileges one category of difference, makes other marginalised groups doubly invisible. Moreover, statistics demonstrate that despite privileging gender over other factors of exclusion, women’s participation remains marginal. Further, it causes the groups at the bottom to compete rather than cooperate, while still falling short of addressing the informal patterns of prejudice and discrimination that keep the majority of the marginalised on the fringes of public life.This research proposes the intersectionality approach to policy design to simultaneously promote political participation of the various groups. Intersectionality recognises the role of the various categories of difference as equally important yet conceptually different, examines the relationship between the various categories, and emphasises the interaction between individual and institutional factors in achieving equality. Intersectionality, therefore, provides the most effective approach to diagnosing the factors fuelling exclusion and ultimately providing an effective prescription.